Investigation of the reaction of the Direct Synthesis of alkoxysilanes and organoalkoxysilanes from silicon, alcohols and ethers by quantum chemistry methods. - S. P. Knyazev; A. D. Kirilin; E. A. Chernyshov; P. A. Storozhenko (Тонкие химические технологии, 2009)
The molecular and electronic structures and thermodynamic parameters of the reagents and the products of the Direct Synthesis Reaction of alkoxysilanes and organoalkoxysilanes from silicon, alcohols and ethers were calculated by the Hartree-Fock, DFT (including B3LYP/6-311+G**) and other methods of computational chemistry.